Nano Online 2016
DOI: 10.1515/nano.11671_2015.114
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of carbyne: experiment and simulations

Abstract: The results of the high-field technique for obtaining and testing the carbyne strength in situ are presented. By using molecular dynamics simulation and ab initio calculations, a comprehensive analysis of the results is executed. High-field technique for experimental measurement of the carbyne strength in situ is briefly described. It is shown that the technique used gives a lower estimation for strength of carbyne, which equals 251 GPa at T = 77 K. This value is close to the strength 7.85 nN (250 GPa) of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…While the chain length is fixed, the optimization process focuses only on the radial direction of the CNT. An isolated long LCC is always unstable in a room-temperature environment due to strong atomic fluctuations [10][11][12][13][14][15]. The kink angle is a measure of the atomic fluctuations in the LCC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While the chain length is fixed, the optimization process focuses only on the radial direction of the CNT. An isolated long LCC is always unstable in a room-temperature environment due to strong atomic fluctuations [10][11][12][13][14][15]. The kink angle is a measure of the atomic fluctuations in the LCC.…”
Section: Discussionmentioning
confidence: 99%
“…If all covalent bonds in the LCC are stable, the LCC with a length of 15000 atoms should have weaker atomic fluctuations than the LCC with a length of 6000 atoms. However, extensive studies of LCC show that the elongation of LCC always leads to chain termination or self-dissociation [10][11][12][13][14][15]25,27]. So far, the formation of all stable covalent bonds in an extremely long LCC has not been observed experimentally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2015, Kotrechko et al demonstrated that an acetylenic carbon chain of 44 units could be synthesized in a stable form both via simulations and initial experimental syntheses. Furthermore, they found that carbyne's tensile strength (393 GPa) and Young's modulus (4.6 TPa) were indeed the highest of any known material in the world [3]. Shortly after this work, Shi et al (2016) devised a method for synthesizing carbyne in high purity, chain length, and yield; by growing carbyne inside of double-walled carbon nanotubes (DWCNTs), the acetylenic chains become highly stable and protected from the external environment by their nanoscaffolds [4].…”
Section: Introductionmentioning
confidence: 99%